Implementation Barriers of Electronic Health Record Interoperability in Indonesian District Hospitals: A Mixed-Methods Study - Septien Dwi Savandha; Elvira Fitriyanti; Adelia Azzahra (Indonesian Health Journal, 2026)
The implementation of interoperable Electronic Health Records (EHRs) is essential for strengthening integrated, patient-centered healthcare delivery in Indonesia; however, district hospitals continue to face substantial barriers in aligning local hospital information systems with the national SATUSEHAT platform. This study aimed to identify and analyze the technical, organizational, regulatory, and human resource barriers affecting EHR interoperability readiness in Indonesian district hospitals. A convergent parallel mixed-methods design was employed across 12 type C and D district hospitals in West Java, Central Kalimantan, and East Nusa Tenggara. Data collection was conducted during the e januari-maret period in 2025. Quantitative data were collected from 240 respondents using a structured questionnaire based on the Technology-Organization-Environment framework and the Unified Theory of Acceptance and Use of Technology, while qualitative data were obtained through interviews and focus group discussions with 36 key informants. The findings showed that vendor and system interoperability, technical infrastructure readiness, and human resource competency were the most critical barriers. Logistic regression indicated that low infrastructure readiness, weak vendor interoperability, limited digital literacy, lower hospital digital maturity, and geographic location significantly predicted low interoperability readiness. Qualitative findings further revealed vendor lock-in, unstable connectivity, limited training, budget constraints, and regulatory implementation gaps. In conclusion, EHR interoperability in Indonesian district hospitals requires not only technical standardization, but also sustained organizational support, workforce capacity-building, stronger vendor governance, and differentiated policy assistance for hospitals with lower digital maturity. This study is novel in that it applies a convergent parallel mixed-methods design integrating the TOE and UTAUT frameworks specifically at the district-hospital level (RSUD type C and D) across provinces with contrasting digital maturity, an analytical scope that has not been jointly examined in prior Indonesian EHR interoperability research.